INFLUENCE OF CRYSTALLITE SIZE ON THE ELECTRICAL PROPERTIES OF ZNO AND CUO THIN FILMS (Global Conference on Multidisciplinary Research and Innovation, 2026)
The structural characteristics of semiconductor thin films play a crucial role in determining their electrical and functional behavior. Among various microstructural parameters, crystallite size significantly influences charge transport mechanisms, carrier mobility, grain boundary effects, and electrical conductivity of oxide semiconductor materials. ZnO and CuO thin films are widely used in optoelectronic devices, photovoltaic systems, sensors, and nanoelectronic technologies due to their favorable semiconductor properties.